If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18a + b + -3a + 14b = 0 Reorder the terms: 18a + -3a + b + 14b = 0 Combine like terms: 18a + -3a = 15a 15a + b + 14b = 0 Combine like terms: b + 14b = 15b 15a + 15b = 0 Solving 15a + 15b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-15b' to each side of the equation. 15a + 15b + -15b = 0 + -15b Combine like terms: 15b + -15b = 0 15a + 0 = 0 + -15b 15a = 0 + -15b Remove the zero: 15a = -15b Divide each side by '15'. a = -1b Simplifying a = -1b
| 1+2x=-23-4x | | 81+81+81= | | 2(5x+2)=-16 | | x(.75)=55000 | | 30+30+30+30= | | X+75+x=153 | | (5x-3)(4x+5)=0 | | 25^2/x=5 | | 8x-13+5x=5+9x+14 | | 9x+1.28=3x+11 | | -11-y=1 | | y^2+2h=35 | | y=2.5(3)+3 | | 0.3x+0.6=-1.8 | | y=2.5(2)+3 | | 1-Y+2Z=3 | | X+75+x=159 | | 2r^2-5t=12 | | -5y+10=55 | | y=2.5(1)+3 | | y=2.5(0)+3 | | 3(4-2d)-6=(5d-5) | | 2(3x-7)=8x-28 | | ((-3x^2)+144)=0 | | 8x-13+5x=5+9x+6 | | 6.9a+6.52=-57.65 | | q=2p+4 | | y=2.5(-1)+3 | | 2h+8=18 | | (5+6i)+(4i-10)=0 | | 9x-11=3x+19 | | 10t+14=10t+14 |